Stochastic Bus Dispatching Model untuk Optimalisasi Jumlah Bus Transjakarta Koridor 3 - Zahedi, Zahedi; Wijaya, Fredy (Bina Nusantara University, 2011)
The increasing number of road user causing traffic jam finds out a way, busway. However, in its implementation, the number of fleet available does not enough to take the passengers. It results in the an amassed of passengers at several bus stops. This leads to passenger dissatisfaction satisfaction which eventually causes Transjakarta users to reuse private cars. Definitely this situation may builds up traffic jams. Stochastic Bus Dispatching Model is used to simulate public transportation that operates regularly.